Physico-Chemical Properties, Chemical Composition and In Vitro Antimicrobial and Free Radical-Scavenging Capacity of Tea Tree Essential Oil in Thailand - Udomlak Sukatta,; Prapassorn Rughtaworn,; Olarn Tuntawiroon,; Weerasri Meaktrong, (Agriculture and Natural Resources, 2011)
The physico-chemical properties, chemical composition and in vitro antimicrobial and free radical-scavenging capacity of Tea Tree essential oils (TTOs) from three regions of Thailand were studied. The physico-chemical properties of the TTOs obtained by hydro distillation had specific gravity at 20 °C, refractive index at 20 °C and optical rotation values of 0.900–0.905, 1.475–1.481 and 5.25–6.15°, respectively. Based on characterization by gas chromatography-mass spectrometry (GC-MS), the chemical composition of the main constituents of the TTOs were terpinen-4-ol (30.42–34.76%), γ-terpinene (25.08–26.23%), α-terpinene (12.31–12.43%) and 1,8-cineole (5.99–9.08%). The TTOs exhibited strong antibacterial activity against Staphylococcus aureus (DMST 8840) (MIC 0.064–0.512 mg/mL; MBC 0.128–0.512 mg/mL) and showed interesting antibacterial activity against Vibrio cholerae (DMST 15778), Bacillus cereus (TISTR 687). The Tea Tree essential oils showed high antifungal activity against Chaetomium globosum (TISTR 3093). (AI = 82.76–87.04%) and partially inhibited the growth of Curvularia lunata (TISTR 3289), Aspergillus flavus (TISTR 3366), Aspergillus niger (TISTR 3245) and Penicillium sp. (TISTR 3046). The free radical-scavenging capacity of the essential oil was investigated using 2,2-diphenylpicryl-hydrazyl (DPPH) radical scavenging assay, The TTOs showed strong antioxidant activities (IC50 29.34–38.68 mg/mL). The results suggest that TTOs in Thailand had the same quality as in Australia and could be a natural antibacterial and antioxidation agent.